Screened realities: a Grounded Theory exploration of gaming disorder dynamics among Iranian male adolescents - Mazaherizadeh, Ali; Taherifar, Zahra; Farahani, Hojjatollah; Hussain, Zaheer (Frontiers in Psychiatry, 2024)
Introduction The increasing prevalence of gaming Disorder (GD) among adolescents has become a global concern. Despite the rising number of studies investigating GD, the cultural and socio-economic factors influencing GD with a qualitative approach are scarce. This study aims to explore the underlying factors, processes, and consequences of GD among Iranian male adolescents and contextual factors related to GD within Iran's unique socio-cultural and psychological tapestry. Methods The study used a qualitative design based on the Grounded Theory Method (GTM). The researchers conducted semi-structured interviews with 13 male adolescents aged 15-18 who Dignasoed according to DSM-5 and ICD-11 criteria. The interviews were transcribed and analyzed using the GTM approach, which involves open, axial, and selective coding. Results The study revealed nine main themes and a core category: (1) interaction seeking, (2) encounter and familiarize with games, (3) games attraction, (4) Socialization, (5) game careerism, (6) dexterity, (7) lack and compensation, (8) physical harm, territorial-cultural barrier, (9) second life, and ''life crafting'' as the core category. Discussion The study's findings provide valuable insights into the cultural and socio-economic factors influencing GD among Iranian male adolescents. For example, Iran's economic conditions make adolescents choose gaming as their job and try to earn money in this way, which makes them more dependent on gaming. On the other hand, communities related to games play an essential role in the identity development of adolescents with GD.